The Sanitation Triangle Socio-Culture, Health and Materials - Yamauchi, Taro.; Nakao, Seiji; Harada, Hidenori; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This open access book deals with global sanitation, where SDG 6.2 sets a target of enabling access to sanitation services for all, but has not yet been achieved in low- and middle-income countries. The transition from the United Nations MDGs to the SDGs requires more consideration based on the socio-cultural aspects of global sanitation. In other words, equitable sanitation for those in vulnerable situations could be based on socio-cultural contexts. Sanitation is a system that comprises not only a latrine but also the works for the treatment and disposal of human waste. Sanitation systems do not function by themselves but have significance only through social management. The process of decision-making also largely depends on socio-cultural conditions, and the importance of sanitation needs to be socially acknowledged. The health benefits of sanitation improvement$1 (Bamong the significant contributions of sanitation$1 (Balso need to be considered in the socio-cultural milieu. Further, the social-culture itself is affected, and potentially even created, by sanitation. In this context, more progress on the improvement of sanitation requires a more holistic approach across disciplines. In this book, we present the concept of the Sanitation Triangle, which considers the interconnections of health, materials, and socio-culture in sanitation, as a holistic approach, and the case studies based on the Sanitation Triangle by diverse disciplines such as Cultural Anthropology, Development Studies, Health Sciences, Engineering, and Science Communication. By the deep theoretical examinations and inter-dialogues between the different disciplines, this book explores the potentialities of inter-disciplinary studies on global sanitation.s
Introduction -- Part I Socio-Culture -- Chapter 1: Socio-Cultural Aspects of Sanitation -- Chapter 2: Ideas and Practices for Restoring the Humanity of Sanitation Workers in India -- Chapter 3: Dissociation between National Policy and Local Communities in regard to Water Supply Management -- Chapter 4: Gender and Culture Matters: Considerations for Menstrual Hygiene Management -- Part II Health -- Chapter 5: Interactions between Health and Socio-Culture in Sanitation -- Chapter 6: Influence of Water, Sanitation, and Hygiene (WASH) on Children$1 (Bs Health in an Urban Slum in Indonesia -- Chapter 7: Social Allocation of the Health Risks in Sanitation -- Chapter 8: Participatory Action Research for WASH by Children and Youth in Peri-Urban Communities -- Part III Materials -- Chapter 9: Interactions between Materials and Socio-Culture in Sanitation -- Chapter 10: Social Integration and Acceptance of Emerging Sanitation Infrastructure in Japan -- Chapter 11: Acceptability of Urine-Diversion Dry Toilets and Resource Values of Excreta in Rural Societies -- Chapter 12: Social Relationships and Material Flow in the Co-Creation of Sanitation Systems -- Conclusion.s
Keywords: Environmental health; Environment; Environmental sciences$1 (BSocial aspects.s; Environmental management; Environmental Health; Environmental Sciences; Environmental Social Sciences; Environmental Management